Necrotising Myositis, the Deadly Impersonator - A. Rahman; A. K. Abou-Foul; A. Yusaf; J. Holton; L. Cogswell (Case Reports in Surgery)
We report two cases of patients with necrotising myositis who presented initially with limb pain and swelling on a background of respiratory complaints. Patient 1, a previously well 38-year-old female, underwent various investigations in the emergency department for excessive lower limb pain and a skin rash. Patient 2, a 61-year-old female with a background of rheumatoid arthritis and hypertension, presented to accident and emergency feeling generally unwell and was treated for presumed respiratory sepsis. Both deteriorated rapidly and were referred to the plastic surgery team with soft tissue necrosis, impending multiorgan failure and toxaemia. Large areas of necrotic muscle and skin were debrided, which grew group A streptococci, Streptococcus pyogenes. Patient 1 had a high above knee amputation of the left leg with extensive debridement of the right. Despite aggressive surgical intervention and microbiological input with intensive care support, patient 2 died. These two cases highlight the importance of early diagnosis and prompt surgical and pharmacological intervention in managing this life-threatening disease. Pain is the primary symptom with skin changes being a late and subtle sign in a septic patient. The Laboratory Risk Indicator for Necrotising Fasciitis (LRINEC) may be of use if there is concern to aid diagnosis of this life-threatening disease.